Principal's Leadership Style in Improving Teacher Performance at Muhammadiyah Plus Junior High School of Salatiga - Cahyono, Guntur; Kardoyo, Kardoyo; Hardyanto, Wahyu; Mahmud, Amir (Universitas Negeri Semarang, 2024)
This study holds significant importance as it is based on the ongoing improvements and achievements received by the students, teachers, and Muhammadiyah Plus Junior High School of Salatiga institution. The school principal's leadership style, a crucial factor in these achievements, is one of the attempts to develop the charity work of Muhammadiyah in the education field. This study aims to identify the leadership styles adopted in the school to enhance the teachers' performances. It applied a qualitative approach by employing interviews and other relevant resources to this study. The collected data revealed that the transformative leadership style is identified as the leadership style that was adopted by the Muhammadiyah Plus Middle School principal. The applied leadership style has impacted the well-established teacher performance, which is proven by the huge number of achievements received by the students, teachers, and school institutions. Thus, the leadership style that has been adopted by the school principal has impacted optimal teacher performance in the teaching-learning process and improved achievements through the supporting facilities that the school continues to strive for. Teacher performance continues to improve by building a common vision between the foundation, school principals, and teachers.